Nonlocal Wave Propagation in Unbounded Multi-Scale Media (Communications in Computational Physics, 2020)
This paper focuses on the simulation of nonlocal wave propagations in unboundedmulti-scale mediums. To this end, we consider two issues: (a) the designof artificial/absorbing boundary conditions; and (b) the construction of an asymptoticallycompatible (AC) scheme for the nonlocal operator with general kernels. The designof ABCs facilitates us to reformulate unbounded domain problems into boundeddomain problems. The construction of AC scheme facilitates us to simulate nonlocalwave propagations in multi-scale mediums. By applying the proposed ABCs andthe proposed AC scheme, we investigate different wave propagation behaviors in the"local" and nonlocal mediums through numerical examples.
Keywords: Asymptotically compatible; absorbing boundary method; nonlocal wave equation; nonlocal wave propagation; multi-scale mediums.